The Ube (“Roots”) Generation - Velasco, Tabitha Espina (Humanities Diliman: A Philippine Journal of Humanities, 2016)
Filipino people comprise the second-highest percentage of the population in Guam, and this local trend mirrors that of the mainland United States. Using the metaphor of ube, I use the term “ube” to characterize the generation of my grandmother—the initial generation in their families to immigrate to Guam from the Philippines, after the post-WWII migration surge. I term this generation the Ube (“Roots”) generation and describe how those in this generation use narrative as an attempt to negotiate their identities in new surroundings. Using an autoethnographic methodology, I interview my maternal grandmother, Ruthie Caser. I supplement this interview with (1) Caser’s letters, (2) the diary entries of her mother, Rebecca Alvarez, which reference Caser’s transnational relations between Guam and the Philippines, (3) a personal interview with Bernadette Provido, who was petitioned by her husband in connection with Camp Roxas, and (4) the responses in a 1976 survey of attitudes of Filipinas in Guam by Loida C. Retumban. By examining the experiences of the Ube generation through the personal telling of their own stories, I investigate the ways in which they reconcile their Filipino culture with the local and American cultures of Guam. I nevertheless maintain the caveat that my intention is not to determine the extent to which these immigrants retain their original culture or adopt the American culture. Rather, I hope to depict the process whereby they maintain and preserve aspects of their Filipino “roots,” while transforming and being transformed by their new landscape. This paper is part of a series, “Palatable Experiences: Identity Formation in the Narratives of Three Generations of Filipinas on Guam,” which examines the identities of the Ube Generation, the Sapin-Sapin (“Layers”) Generation, and the Halo-Halo (“Mix Mix”) Generation. Keywords: Guam, Filipina, autoethnography, narrative, generation identity